Moda, msica y deporte - Ortiz Estacio, Omar Enrique (2019)
The present work professional sufficiency entitled Fashion, music and sport, aims to support and argue through the application of a learning session to the students of the third year of the I.E. Fray Martin de Porres._x000D_ The adolescents of today have lost the great importance of identifying the types of fashion that happens in their age as such, in response to this need arises to inform students how to identify the types of fashion rate their personal characteristics._x000D_ For this, a great diversity of learning strategies such as motivation, previous knowledge, cognitive conflict among others has been used. That they manage to awaken interest in students in order to be used by them._x000D_ The present work consists of three parts, in the first part the methodological strategies of the application of the learning session have been elaborated, in the second presentation the scientific support whit the help of the support quotes and the third, the psych pedagogical sustenance